Napoleon's Italian campaigns : 1805-1815 - Schneid, Frederick C. (Praeger, 2002)
The French Revolutionary and Napoleonic wars raged in Italy for 23 years. In that time, no fewer than eight campaigns involving hundred of thousands of troops were mounted in the Italian peninsula, as France and Austria struggled over this secondary, but still vitally important theater of war. As Frederick Schneid demonstrates in this groundbreaking work, control of Italy was rightly seen by Napoleon as an important means of applying strategic pressure on the Austrians, while simultaneously providing security for France's vulnerable southern flank. As the first in-depth consideration of the struggle for strategically key region, this book places the Italian campaigns into their proper historical context.